2011
DOI: 10.1590/s0101-31222011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Secagem e armazenamento de sementes de sorgo com alto e baixo teor de tanino

Abstract: 5rESUMo -o teor de água em que a semente é colhida, bem como a temperatura utilizada para a secagem, é fundamental para garantir a qualidade fisiológica das sementes, principalmente as de sorgo, que podem apresentar dormência secundária, por secagem em altas temperaturas. Com a realização deste trabalho, objetivou-se avaliar a qualidade fisiológica das sementes de sorgo, com alto e baixo teor de tanino e armazenadas após secagem, utilizando diferentes temperaturas. Foram utilizadas sementes das cultivares br 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
9
0
4
Order By: Relevance
“…Oliveira et al (2011) constataram, para as sementes de sorgo da cultivar BR 305, que o maior valor de germinação ocorreu com sementes secadas sob temperatura de 45 °C, quando estudaram a secagem das sementes à sombra e em protótipos de secadores estacionários, regulados nas temperaturas de 35°, 45° e 35/45 °C.…”
Section: Resultsunclassified
“…Oliveira et al (2011) constataram, para as sementes de sorgo da cultivar BR 305, que o maior valor de germinação ocorreu com sementes secadas sob temperatura de 45 °C, quando estudaram a secagem das sementes à sombra e em protótipos de secadores estacionários, regulados nas temperaturas de 35°, 45° e 35/45 °C.…”
Section: Resultsunclassified
“…As observed in this research, extreme conditions of temperature have been reported to be able to bring about dormancy in seeds as a defense mechanism to preserve seed viability under adverse conditions (MARCOS-FILHO, 2005;VIVIAN et al, 2008;OLIVEIRA et al, 2011;NAKAGAWA, 2012). This is an important information for parsley seeds, since factors associated with the occurrence of dormancy in parsley seeds have not been clarified and the dormancy of those seeds is a common problem for the production of this species, causing tardiness and low uniformity in seedling emergence (TRINCA, 2007).…”
Section: Resultsmentioning
confidence: 73%
“…According to this experiment, variations in germination and emergence may be due to overcoming dormancy, which naturally occurs during storage of sorghum seeds (Oliveira et al, 2011 show better quality compared to conservation in dry chamber. On the other hand, Oliveira et al (2011) found that cold temperatures during storage may increase seed dormancy. In any way, it is uncertain if dormancy is accentuated by cold-temperature storage or reducing of phenolic compounds.…”
Section: The Equation Adjusted To Mean Germinationmentioning
confidence: 93%
“…Seeds are one of the most important inputs in agriculture; among all production stages, storage is a mandatory concern, mainly in Brazilian subtropical and tropical conditions (Souza et al, 2009). According to Oliveira et al (2011), studying behavior of seeds during storage, as well as biochemical changes and accumulation of secondary components, may bring relevant information to be applied in quality maintenance.…”
mentioning
confidence: 99%